Análise das mutações C288Y, S65C e H63D e frequência alélica do gene HFE em pacientes com hiperferritinemia, em uma cidade do Nordeste, Brasil - Leão, Gioconda Dias Rodrigues (2013)
Background & Aims: HFE-associated Hereditary Hemochromatosis (HH) is one of the most frequent autosomal recessive disease in the caucasian population, caused by the high absorption and deposition of iron in several organs. This accumulation results in several clinical complications such as cirrhosis, arthritis, cardiopathies, diabetes, sexual disorders and skin darkening. Although most of the cases are homozygous individuals for the C282Y mutation, another two mutations, H63D and S65C, have been reported to be associated with milder forms of the disease. The objective is to avaluate the distribution of C282Y, H63D and S65C mutations in the HFE gene in patients with suspected HH in the state of Rio Grande do Norte, Brazil. Methods: Samples of peripheral blood were taken from 335 patients originating from Natal-RN, a city in northeastern Brazil with suspected of HH and which were screened for the HFE gene C282Y, H63D and S65C mutations, using molecular genetics assays (Polymerase Chain Reaction- Restriction Fragments Length Polymorphism). The main criterion for including such patients in the study was the increasing of persistent serum ferritin in individuals aged between 18 and 70 or older, both males and females. As to the exclusion criteria, individuals holding hemolytical anemia, talassemy and previously report of blood transfusion did not take part of the study. Results: Out of the 335 patients studied, 143 patients showed absence of mutation and 195 showed some kind of mutation in the HFE gene: 07/335 (2,08%) were homozigous C282Y, 25/335 heterozygous C282Y, 25/335 (7,46%) were homozigous H63D, 115/335 (34,32%) heterozygous H63D, 5/335 (1,48%) heterozygous S65D, 11/ 335 (3,28%) and were double heterozygous (H63D/C282Y). None patients were Homozygous S65D and S65D heterozygous (S65D/H63D and S65D/C282Y). Conclusions. The distribution of the HFE gene C282Y, H63D and S65C mutations found in our group matches the tendencies observed in other European countries. Due to the high prevalence of hemochromatosis, its seriousness and easy treatment, the genetic diagnosis of HH has become a dream, especially in the high risk group.